Utility of Agri Clinic and Agricultural Business Center Training contents for Agripreneurs in Uttar Pradesh (Indian Journal of Extension Education, 2024)
Ministry of Agriculture and Farmers’ Welfare in India, aims to empower rural youth with agricultural backgrounds to establish their own agricultural enterprises and support farmers. The research, conducted from March to September 2021, focused on assessing the effectiveness of training courses offered by the nodal institute, Shree-Maa-Guru Gramodhyog Sansthan in Varanasi, Uttar Pradesh. A total of 100 respondents were selected for this study and data were collected through a pre-tested structured interview schedule. It was found high utility indices in the entrepreneurial development phase for characteristics and presentation skills (52.0), entrepreneurial management phase for case studies (65.2), and enterprise planning phase for exposure visits and type of organization was perceived high utility (66.2). Animal husbandry comprised 46 per cent of established enterprises, while crop production and nursery activities constituted 20 per cent. Most agripreneurs had little to no work experience (55%). Major challenges included social stigma (60%), market fluctuations (59%), price factors (40%), and unpredictable climatic conditions (33%). The study suggests a holistic approach to refining the ACABC program, ensuring it aligns with the dynamic requirements of agripreneurs in Uttar Pradesh. This approach involves content enrichment, digital literacy promotion, strategic management emphasis, experiential learning, local opportunities exploration, resource mobilization enhancement, customization, and continuous evaluation.